XEROSTOMIA IN ORAL MEDICINE: UNDERLYING ETIOLOGIES, CLINICAL CONSEQUENCES, AND MANAGEMENT STRATEGIES - Toshpulatova Odina Shavkatovna, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: Xerostomia, or dry mouth, is a common condition that can occur when saliva production is reduced, although some people may feel dryness even with normal saliva levels. it is especially common in older adults and is often caused by medications, certain diseases, or treatments, such as radiotherapy to the head and neck. dry mouth can make everyday activities, particularly speaking, eating, and swallowing uncomfortable, and it can increase the risk of tooth decay and oral infections. diagnosis is based on both the patient’s experience and clinical tests that measure saliva flow. management focuses on treating the underlying cause, relieving symptoms, and preventing complications. early recognition and proper care are important for maintaining comfort and oral health.